THE MONITORING OF ECONOMIC SECURITY OF THE ORGANIZATION - V. Lokhanova (Вестник университета)
In the article the concept of monitoring of economic security of the organization is defined from the point of view of its relevance and functionality. Peculiarities of legal, organizational, methodological, informational and technical support of monitoring. Drafted organizational scheme of monitoring, including selected stages of its design and implementation as a business process. Special attention is paid to feedback in the monitoring mechanism. Formulated efficiency indicators monitoring, identifying possible problems.